Determinants and outcomes of motivation in health professions education: a systematic review based on self-determination theory - Cesar Orsini; Vivian I. Binnie; Sarah L. Wilson (Journal of Educational Evaluation for Health Professions, 2016)
Purpose: This study aimed at conducting a systematic review in health professions education of determinants, mediators and outcomes of students’ motivation to engage in academic activities based on the self-determination theory’s perspective. Methods: A search was conducted across databases (MEDLINE, CINHAL, EMBASE, PsycINFO, and ERIC databases), hand-search of relevant journals, grey literature, and published research profile of key authors. Quantitative and qualitative studies were included if they reported research in health professions education focused on determinants, mediators, and/or outcomes of motivation from the self-determination and if meeting the quality criteria. Results: A total of 17 studies met the inclusion and quality criteria. Articles retrieved came from diverse locations and mainly from medical education and to a lesser extent from psychology and dental education. Intrapersonal (gender and personality traits) and interpersonal determinants (academic conditions and lifestyle, qualitative method of selection, feedback, and an autonomy supportive learning climate) have been reported to have a positive influence on students’ motivation to engage in academic activities. No studies were found that tested mediation effects between determinants and students’ motivation. In turn, students’ self-determined motivation has been found to be positively associated with different cognitive, affective, and behavioural outcomes. Conclusion: This study has found that generally, motivation could be enhanced by changes in the educational environment and by an early detection of students’ characteristics. Doing so may support future health practitioners’ self-determined motivation and positively influence how they process information and their emotions and how they approach their learning activities.